Emission factors of industrial boilers burning biomass-derived fuels. (3rd April 2023) - Bhatt, Arpit; Ravi, Vikram; Zhang, Yimin; Heath, Garvin; Davis, Ryan; Tan, Eric C.D.
ABSTRACT: Boilers are combustion devices that provide process heat and are integral to many industrial facilities. Historically, outside of the pulp and paper industry, most boilers burned fossil fuels, although interest in decarbonization has been leading to an increased use of renewable fuels in boilers. These boilers, including those in the biorefineries, are often large sources of air pollutant emissions, and the characterization of these emissions is critical to obtaining air permits and ensuring protection of the surrounding air quality. Several industrial boilers and new biorefineries allow utilization of biomass-derived fuels (e.g. wastewater sludge, lignin, etc.) produced during their operation as a fuel for the boiler to meet process energy needs. However, there is limited empirical data on emission factors for the burning of unconventional fuels, such as solid-gas mixtures containing biomass residues. To fill this gap, we carry out a comprehensive data survey, collecting information on emission factors for boilers burning either a single or a mixture of solid and gaseous biomass-derived fuels. We review multiple hard-to-obtain and unconventional data sources, such as air permit applications, stack test data, and industry-sponsored data collection efforts, to compile emission factors for biomass-derived fuels. We then compare this data with wood residue emission factors from the U.S. Environmental Protection Agency's AP-42 emission factor database. Our results indicate that the emission factors for boilers burning unconventional fuels vary widely depending on the fuel composition, boiler type, and fuel characteristics. Overall, we find that median emission factors of selected biomass-derived fuels are typically lower than those of wood residue boilers in AP-42. The information collected herein could be useful to permitting agencies and industries utilizing boilers who may want to reduce the carbon impact of their facilities by combusting biomass-derived wastes for process energy needs, for more accurate emission estimation for permitting. Implications: Emission factors are often used for air permitting, specifically for emission estimation purposes. This study carries out a comprehensive data survey of emission factors burning unconventional biomass-derived fuels from underutilized sources such as air permits, stack test data, and industry-led efforts, and compare the results to EPA's wood residue emission factor database. The results from this study can be used can be used by multiple stakeholders such as air permitting agencies, industries burning biomass-derived fuels, and biorefineries, that utilize more advanced boiler technologies. The findings can help mitigate risks to industry owners and operators and helps to avoid delays in obtaining the required air permits that arise due to inappropriate emission estimates in permit applications.